SISTEM INFORMASI DOKTER SPESIALIS RSUP DR. KARIADI SEMARANG BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract : Health services in hospitals needs to be improved in terms of scheduling specialists so that the desired information more easily available and efficient. At this time, almost all information on hospital services are still handled by the officers keeping the counter and space information. Along with the development of increasingly sophisticated smartphones, then possible to replace it with a more untouched technology facilities. This research aims to make information systems on schedule doctor on duty at the hospital specialist Dr. Kariadi Results of the application making the department of information systems specialist Dr. Kariadi Android-based Android is distributed to RSUPDr.KARIADI.apk installer file. This application is expected to help officers and visitors Hospital Dr. Kariadi in finding information specialist. Keywords: Specialist Doctor, Hospital Dr. Kariadi, android